Effect of electric current direction on the microstructural evolution and mechanical properties of a cold-rolled Cu–Zn alloy during the phase transformation induced by electric current pulses. Issue 16 (7th August 2015) - Wang, Xinli; Liu, Meishuai; Dai, Wenbin; Wu, Nan; Zhao, Xiang
Abstract: Abstract : The effect of current direction (CD) on the microstructural evolution and mechanical properties of a Cu–Zn binary phase (α + β) alloy during the primary process of phase transformation induced by electric current pulses (ECP) treatment was investigated. To clarify the effect of CD, the samples were prepared with different angles between the CD and rolling direction (RD) from 0° to 90°. Results showed that not only the microstructural evolution but also the corresponding mechanical properties all had a saddle point in the sample with the angle 45°. Analyzed from the mechanical properties, it could be found that the anisotropic of the materials becomes stronger due to the application of ECP. An important finding is that by changing the angles between the CD and the RD, a novel and effective approach to control the phase transformation process could be provided.